Questão de gênero e MST : os coletivos de auto-organização das mulheres no Espírito Santo - Amaral, Maísa Maria Baptista Prates do (2018)
This dissertation aims at analyzing how the MST women's self-organization groups in Espírito Santo contribute to a greater insertion of women in the social and political spaces of the Movement itself and to advancing the gender issue and overcoming the sexual division of the job. We have, therefore, as object of analysis, two collective self-organized around the construction of two agroindustries in two different settlements: "Camponesas" of the Settlement of the Vale da Esperança, and "As Camponesas" of the Settlement Florestan Fernandes. In order to do so, we use as theoretical reference the Marxist Theory of Dependence, which allows us to understand how Latin America, and specifically Brazil, is inserted in the international division of labor and how the transfer of value from the peripheral economies to the central ones, with the overexploitation of the labor force as the only form of peripheral economies to develop. Thus, starting from this referential, we also try to understand how gender relations and the sexual division of labor, while functional to capital, are experienced by these women and the role of the MST women's self-organization in the attempt to change this reality. For this, we used as the focal group as data collection technique and content analysis as data analysis technique. The theoretical categories that guided our research and our analysis were Agrarian Issue and Dependency, Gender Relations and Sexual Division of Labor.